Vitexin alleviates inflammation and enhances apoptosis through the regulation of the JAK/STAT/SOCS signaling pathway in the arthritis rat model. Issue 12 (27th August 2022) - Zhang, Daojian; Ning, Taiguo; Wang, Hongbin
Abstract: Rheumatoid arthritis (RA) is a chronic inflammatory and autoimmune disorder. RA is progressive and needs long‐term treatment. Vitexin is a naturally‐occurring flavonoid that is identified in various plant sources. Vitexin is demonstrated to produce antioxidant effects with numerous pharmacological activities. This experimental in vivo study assessed the antiarthritic and apoptotic role of a natural plant extract, vitexin, on RA. Collagen‐induced arthritis (CIA) rat model Sprague Dawley males were grouped into five sets with six rats each: control, CIA, CIA + vitexin (10 mg/kg bw), CIA + Methotrexate (1 mg/kg bw), and vitexin (10 mg/kg bw) alone. The body weight, organ weight, biochemical assay, inflammatory enzymes, apoptosis, and cytokines levels were evaluated and compared among groups. Janus kinase (JAK)/signal transducer and activator of transcription (STAT)/suppressors of cytokine signaling (SOCS) levels and histopathology of ankle joints were also studied and compared. Significance was considered at a p < 0.05. Vitexin (10 mg/kg bw) significantly reduced the inflammatory enzyme markers, interleukin (IL)‐1β, IL‐6, IL‐17, IL‐4, IL‐10, tumor necrosis factor‐α, interferon‐γ, and iNOS levels in arthritis rats ( p < 0.05). Vitexin significantly improved collagen‐induced arthritic histological changes ( p < 0.05). Vitexin also reduced JAK/STAT expressions associated with inflammation and significantly increased elevated SOCS levels ( p < 0.05). Aberration in apoptosis, inflammatory mediators, C‐reactive protein, and rheumatoid factor levels in the arthritic rats reverted to normal with vitexin. These results emphasize that vitexin possesses anti‐inflammatory and apoptotic activity via the regulation of JAK/STAT/SOCS signaling in CIA in a rat model. Hence, vitexin is a promising auxiliary drug for RA treatment.